Integrating organic photovoltaics (OPVs) into greenhouses: electrical performance and lifetimes of OPVs. Issue 8 (14th September 2022) - Magadley, Esther; Teitel, Meir; Kabha, Ragheb; Dakka, Mohamad; Friman Peretz, Maayan; Ozer, Shay; Levi, Asher; Yasuor, Hagai; Kacira, Murat; Waller, Rebekah; Yehia, Ibrahim
ABSTRACT: This paper presents the electrical performance of organic photovoltaic modules (OPVs) on top of a polyethylene covered greenhouse high tunnel in a Mediterranean climate. Modules from a previous study were kept on the tunnel and monitored together with new modules with improved connectors installed on the greenhouse roof and on frames adjacent to the greenhouse. Measured module power conversion efficiencies ranged from 1% to 3%. The typical combined output of the modules across the tunnel roof were 105Wh on a sunny day and 81Wh on a cloudy day. Module burn-in period was about 15 days, losing around 36% of its initial efficiency. Ts 80 lifetimes ranged from 7 days to 94 days. Tunnel integration was shown to accelerate module degradation.